Antistatic fabric and preparation method thereof
Antistatic fabrics were prepared by combining modified polyamide, modified multi-wall carbon nanotubes and inorganic silver ion antibacterial agents, which solved the problems of electrostatic accumulation and poor light resistance of synthetic fiber fabrics, and achieved multiple performance improvements in the fabric.
Patent Information
- Application Number
- CN202510131667.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Synthetic fiber fabrics are prone to electrostatic accumulation, affecting the comfort and aesthetics of wearing, and may pose a potential threat to human health. At the same time, they are poor in light resistance, and are prone to decrease in intensity and yellowing under ultraviolet light.
Antistatic fabrics are prepared by melt-spinning using modified polyamide, modified multi-wall carbon nanotubes and inorganic silver ion antibacterial agents. Modified polyamides enhance UV resistance through specific chemical modifications, modify multi-walled carbon nanotubes improve conductivity, and form a crosslinking network to enhance the mechanical properties of the fabric through the addition of silver ions.
The anti-static, ultraviolet aging and flame retardant properties of the fabric are achieved, the conductive and mechanical properties of the fabric are improved, and the protection and convenience of human health are enhanced.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to an antistatic fabric and a preparation method thereof. Background Art
[0002] As an important part of the modern textile industry, synthetic fibers and synthetic fiber fabrics made from them have the advantages of wear resistance, high strength, easy washing and drying, but they also have some significant disadvantages. Among them, static electricity is a major problem; due to the compact molecular structure of synthetic fibers, charges are not easy to conduct between fibers, resulting in static electricity easily accumulating on the fiber surface, which not only causes clothing to absorb dust and hair, affecting the comfort and aesthetics of wearing, but also may pose a potential threat to human health, such as causing skin inflammation, interfering with the normal operation of electronic equipment, etc.; synthetic fibers have poor light resistance, and under long-term sunlight or ultraviolet light, the strength decreases and the color turns yellow; therefore, it is very necessary to develop fabrics with anti-static and anti-ultraviolet aging functions; in addition, the fabrics can also be given flame retardant and other functions to make the fabrics more widely applicable. Summary of the invention
[0003] The purpose of the present invention is to provide an antistatic fabric and a preparation method thereof to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: The invention discloses an antistatic fabric, which is obtained by melt spinning modified polyamide, modified multi-walled carbon nanotubes and inorganic silver ion antibacterial agent.
[0005] As an optimization, the modified polyamide is obtained by grafting 2-chloro-6-vinylpyridine onto polyamide, reacting with 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, removing the methoxy group through boron tribromide, and reacting with 2-diphenylphosphobenzaldehyde.
[0006] As an optimization, the modified multi-walled carbon nanotubes are obtained by grafting tea polyphenols onto multi-walled carbon nanotubes treated with nitric acid and then treated with thionyl chloride, and then reacting with 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol.
[0007] A method for preparing an antistatic fabric comprises the following steps: (1) Weigh polyamide and 2-chloro-6-vinylpyridine in a mass ratio of 1:(2.0-2.5), mix polyamide and n-propanol in a mass ratio of 1:20 to obtain a polyamide solution, mix 2-chloro-6-vinylpyridine, benzoyl peroxide and n-propanol in a mass ratio of 1:(0.02-0.03):(20-30) to obtain a vinyl solution, add the vinyl solution dropwise to the polyamide solution at 85-95°C at a dropping speed of 1 mL / min, stir for 2-2.5 h after the addition is completed, add acetone in an amount of 120-150 times the mass of the polyamide, filter and dry at 50-60°C for 12 h to obtain a pyridine-based polyamide; (2) Pyridine polyamide, 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, bis(triphenylphosphine)palladium dichloride, sodium carbonate, tetrahydrofuran and pure water were mixed in a mass ratio of 1:(2.5-3.0):(2.7-3.3):(5-5.5):(30- 40): (8-10) mixing, under nitrogen protection, heating to 90 ° C for 10-12h, after the reaction, extracting with ethyl acetate, drying with anhydrous sodium sulfate, and vacuum rotary evaporation to obtain methoxy polyamide; methoxy polyamide and dichloromethane are mixed at a mass ratio of 1:20 to obtain a methoxy polyamide solution, and boron tribromide and dichloromethane are mixed at a mass ratio of 1:20 to obtain a boron tribromide solution, under nitrogen protection, at -52 ° C, the boron tribromide solution is added dropwise to the methoxy polyamide solution and stirring is started, the dropping speed is 0.5 mL / min, the stirring speed is 150 r / min, 10wt% dilute sulfuric acid with a mass of 3 times that of boron tribromide is added and stirred for 3 min, filtered and vacuum dried for 12 h to obtain a pre-modified polyamide; (3) Weigh pre-modified polyamide and 2-(diphenylphosphino)benzaldehyde in a mass ratio of 1:(3-3.5), mix pre-modified polyamide, potassium carbonate, and N,N-dimethylformamide in a mass ratio of 1:(3-3.5):20, heat to 90-100°C and stir for 3-4h to obtain a pre-modified polyamide solution, mix 2-(diphenylphosphino)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain 2-(diphenylphosphino)benzaldehyde. aldehyde solution, adding 2-(diphenylphosphine)benzaldehyde solution to the pre-modified polyamide solution at a dropping speed of 1 mL / min, continuing to react at 90-100°C for 3-4 hours after the dropping is completed, cooling to room temperature, adding pure water 10-12 times the mass of the pre-modified polyamide, cooling to 0°C and standing for 2-3 hours, adding acetone 3-4 times the mass of the pre-modified polyamide solution, filtering and drying at 50-60°C for 12 hours to obtain modified polyamide; (4) Pre-modified multi-walled carbon nanotubes, 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol, acetic acid ethanol solution, and formaldehyde aqueous solution were mixed in a mass ratio of 1:(5-6):(3-4), reacted at 80°C for 3-4 hours, filtered, washed with pure water for 3-4 times, and dried at 50-60°C for 12 hours to obtain modified multi-walled carbon nanotubes; (5) Weighing modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent in a mass ratio of 100:(3-5):(0.7-0.9), drying the modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent at 105°C for 24 hours, and then melt-spinning them on a high-speed spinning machine to obtain antistatic fibers, and weaving the antistatic fibers to obtain antistatic fabrics.
[0008] As an optimization, the polyamide model in step (1) is PA6.
[0009] As an optimization, the preparation method of the pre-modified multi-walled carbon nanotubes in step (4) is as follows: pre-treated multi-walled carbon nanotubes, tea polyphenols, ethyl acetate and pyridine are mixed in a mass ratio of 1:4:50:0.1, reacted at 70°C for 8 hours, and after the reaction, centrifuged at 9500r / min, removed the precipitate, washed with pure water for 3-4 times, and dried at 50-60°C for 12 hours to obtain pre-modified multi-walled carbon nanotubes.
[0010] As an optimization, the melt spinning process parameters of step (5) are as follows: a spinning temperature of 260-280°C, a winding speed of 4500m / min, and a draft ratio of 1.25; and the inorganic silver ion antibacterial agent model is DAW502.
[0011] As an optimization, the preparation method of the pretreated multi-walled carbon nanotubes is as follows: multi-walled carbon nanotubes and 68wt% concentrated nitric acid are mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48 hours, and then washed with pure water for 7-8 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride are mixed in a mass ratio of 1:20, refluxed at 70°C for 24 hours, cooled to room temperature, filtered, washed with tetrahydrofuran for 5-6 times, and dried at 50-60°C for 12 hours to obtain pretreated multi-walled carbon nanotubes.
[0012] As an optimization, the multi-walled carbon nanotube model is L-MWNT-1020, purchased from Shenzhen Nanoport Co., Ltd.
[0013] As an optimization, the reaction process of the modified polyamide in step (3) is as follows: .
[0014] As an optimization, the modified polyamide side chain in step (3) contains a nitrogen-phosphorus ligand that can be complexed with a metal, and the schematic chemical formula of the nitrogen-phosphorus ligand complexing the metal is: ; Wherein, M is a metal ion.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the antistatic fabric, the present invention comprises the following steps: firstly, grafting 2-chloro-6-vinylpyridine onto polyamide under the action of an initiator, reacting with 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, removing methoxy groups by boron tribromide, and reacting with 2-diphenylphosphobenzaldehyde to obtain modified polyamide; secondly, grafting tea polyphenol onto multi-walled carbon nanotubes treated with nitric acid and then with thionyl chloride, and reacting with 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol to obtain modified multi-walled carbon nanotubes; and finally, melt-spinning the modified polyamide, the modified multi-walled carbon nanotubes and an antibacterial agent to obtain antistatic fibers, and weaving the antistatic fibers to obtain the antistatic fabric.
[0016] First, polyamide is grafted with 2-chloro-6-vinylpyridine under the action of an initiator, and then reacted with 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester. 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester replaces the chlorine on 2-chloro-6-vinylpyridine to graft 2-amino-4-methoxypyrimidine to the ortho position of the N element on pyridine. Boron tribromide is used to remove the methoxy group to form a hydroxyl group. The hydroxyl group on the pyrimidine and the nitrogen on the pyridine form a chelate ring within the molecule. When subjected to ultraviolet irradiation, light energy can be converted into heat energy, thereby giving the fabric anti-ultraviolet performance; and then reacting with 2-diphenylphosphobenzaldehyde through the reaction of aldehyde group and amino group to form a nitrogen-phosphorus ligand containing a Schiff base. The introduction of phosphorus element can also give the fabric flame retardant performance. Secondly, tea polyphenols are grafted onto multi-walled carbon nanotubes that are first treated with nitric acid and then with thionyl chloride. The σ bonds between carbon atoms in multi-walled carbon nanotubes are formed by covalent bonds between carbon atoms, which can provide a certain degree of electronic conductivity, while the π bonds are formed by p orbitals arranged in the same plane, which have a high degree of electron sharing and can form a π electron cloud region, further enhancing the conductive properties of the multi-walled carbon nanotubes, thereby giving the fabric conductive properties; the surface of the multi-walled carbon nanotubes treated with nitric acid is carboxylated, and then treated with thionyl chloride to make the surface of the multi-walled carbon nanotubes contain acyl chloride groups, which react with the phenolic hydroxyl groups on the tea polyphenols, thereby making the multi-walled carbon nanotubes Tea polyphenols are grafted onto the surface of rice tubes. Tea polyphenols, as a natural polyphenolic substance, have good antioxidant properties and can give fabrics good antioxidant properties. Tea polyphenols react with 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol under the action of formaldehyde, replacing the hydrogen atoms at the C6 and C8 positions of the tea polyphenol A ring. The steric hindrance provided by 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol allows the ortho-hydroxyl group to capture free radicals and prevent them from initiating a new oxidation cycle again, further improving the antioxidant properties of the fabric. At the same time, terpyridine ligands are also introduced; Finally, the modified polyamide, modified multi-walled carbon nanotubes and antibacterial agent are melt-spun to obtain antistatic fibers, and the antistatic fibers are woven to obtain antistatic fabrics. The modified polyamide and modified multi-walled carbon nanotubes both contain ligands that can complex with metal ions. During the melt spinning process, the antibacterial agent provides silver ions to form a cross-linked network between the modified polyamide and the modified multi-walled carbon nanotubes, thereby enhancing the mechanical properties of the fabric. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The polyamide used in the following examples and comparative examples is PA6; the inorganic silver ion antibacterial agent is DAW502; and the multi-walled carbon nanotube is L-MWNT-1020, which were purchased from Shenzhen Nanoport Co., Ltd. Example 1
[0019] A method for preparing an antistatic fabric, comprising the following steps: (1) Weigh polyamide and 2-chloro-6-vinylpyridine in a mass ratio of 1:2.0, mix polyamide and n-propanol in a mass ratio of 1:20 to obtain a polyamide solution, mix 2-chloro-6-vinylpyridine, benzoyl peroxide and n-propanol in a mass ratio of 1:0.02:20 to obtain a vinyl solution, add the vinyl solution dropwise to the polyamide solution at 95°C at a dropping speed of 1 mL / min, stir for 2.5 h after the addition is completed, add acetone 120 times the mass of the polyamide, filter and dry at 60°C for 12 h to obtain a pyridine-based polyamide; (2) Pyridine polyamide, 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, bis(triphenylphosphine)palladium dichloride, sodium carbonate, tetrahydrofuran and pure water were mixed in a mass ratio of 1:2.5:2.7:5:30:8, heated to 90°C for 12 hours under nitrogen protection, and after the reaction, extracted with ethyl acetate, dried over anhydrous sodium sulfate, and evaporated under reduced pressure to obtain methoxy polyamide; methoxy polyamide and dichloromethane were mixed in a mass ratio of 1:20 Mix to obtain a methoxy polyamide solution, mix boron tribromide and dichloromethane at a mass ratio of 1:20 to obtain a boron tribromide solution, add the boron tribromide solution dropwise to the methoxy polyamide solution under nitrogen protection at -52°C and start stirring, the dropping speed is 0.5 mL / min, the stirring speed is 150 r / min, add 10 wt% dilute sulfuric acid (3 times the mass of boron tribromide) and stir for 3 min, filter and vacuum dry for 12 h to obtain a pre-modified polyamide; (3) Weigh pre-modified polyamide and 2-(diphenylphosphine)benzaldehyde in a mass ratio of 1:3, mix pre-modified polyamide, potassium carbonate and N,N-dimethylformamide in a mass ratio of 1:3:20, heat to 100°C and stir for 4 hours to obtain a pre-modified polyamide solution, mix 2-(diphenylphosphine)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain a 2-(diphenylphosphine)benzaldehyde solution, add the 2-(diphenylphosphine)benzaldehyde solution dropwise to the pre-modified polyamide solution at a dropping rate of 1 mL / min, continue to react at 100°C for 4 hours after the addition is completed, cool to room temperature, add pure water 10 times the mass of the pre-modified polyamide, cool to 0°C and stand for 3 hours, add acetone 3 times the mass of the pre-modified polyamide solution, filter and dry at 60°C for 12 hours to obtain a modified polyamide; (4) Multi-walled carbon nanotubes and 68wt% concentrated nitric acid were mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and then washed with pure water for 8 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride were mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran for 6 times, and dried at 60°C for 12h to obtain pretreated multi-walled carbon nanotubes; pretreated multi-walled carbon nanotubes, tea polyphenols, ethyl acetate, and pyridine were mixed in a mass ratio of 1:4:50:0 .1, and react at 70°C for 8h. After the reaction, centrifuge at 9500r / min, remove the precipitate, wash it with pure water for 4 times, and dry it at 60°C for 12h to obtain pre-modified multi-walled carbon nanotubes; pre-modified multi-walled carbon nanotubes, 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol, acetic acid ethanol solution, and formaldehyde aqueous solution are mixed in a mass ratio of 1:5:3, react at 80°C for 4h, filter, wash it with pure water for 4 times, and dry it at 60°C for 12h to obtain modified multi-walled carbon nanotubes; (5) Modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent were weighed in a mass ratio of 100:3:0.7, and the modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent were dried at 105°C for 24 hours, and then melt-spinned on a high-speed spinning machine. The melt-spinning process parameters were as follows: spinning temperature of 280°C, winding speed of 4500 m / min, and draft ratio of 1.25 to obtain antistatic fibers, and the antistatic fibers were woven into antistatic fabrics. Example 2
[0020] A method for preparing an antistatic fabric, comprising the following steps: (1) Weigh polyamide and 2-chloro-6-vinylpyridine in a mass ratio of 1:2.2, mix polyamide and n-propanol in a mass ratio of 1:20 to obtain a polyamide solution, mix 2-chloro-6-vinylpyridine, benzoyl peroxide and n-propanol in a mass ratio of 1:0.025:25 to obtain a vinyl solution, add the vinyl solution dropwise to the polyamide solution at 90°C at a dropping rate of 1 mL / min, stir for 2.3 h after the addition is completed, add acetone 130 times the mass of the polyamide, filter and dry at 55°C for 12 h to obtain a pyridine-based polyamide; (2) Pyridine polyamide, 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, bis(triphenylphosphine)palladium dichloride, sodium carbonate, tetrahydrofuran and pure water were mixed in a mass ratio of 1:2.7:3.0:5.2:35:9, heated to 90°C for 11 hours under nitrogen protection, and after the reaction, extracted with ethyl acetate, dried over anhydrous sodium sulfate, and evaporated under reduced pressure to obtain methoxy polyamide; methoxy polyamide and dichloromethane were mixed in a mass ratio of 1:2 0 to obtain a methoxy polyamide solution, boron tribromide and dichloromethane are mixed at a mass ratio of 1:20 to obtain a boron tribromide solution, the boron tribromide solution is added dropwise to the methoxy polyamide solution at -52°C under nitrogen protection, and stirring is started at a dropping speed of 0.5 mL / min and a stirring speed of 150 r / min, 10 wt% dilute sulfuric acid (3 times the mass of boron tribromide) is added and stirred for 3 min, filtered and vacuum dried for 12 h to obtain a pre-modified polyamide; (3) Weigh pre-modified polyamide and 2-(diphenylphosphine)benzaldehyde in a mass ratio of 1:3.2, mix pre-modified polyamide, potassium carbonate and N,N-dimethylformamide in a mass ratio of 1:3.2:20, heat to 95°C and stir for 3.5 hours to obtain a pre-modified polyamide solution, mix 2-(diphenylphosphine)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain a 2-(diphenylphosphine)benzaldehyde solution, add the 2-(diphenylphosphine)benzaldehyde solution dropwise to the pre-modified polyamide solution at a dropping rate of 1 mL / min, continue to react at 95°C for 3.5 hours after the addition is completed, cool to room temperature, add pure water 11 times the mass of the pre-modified polyamide, cool to 0°C and let stand for 2.5 hours, add acetone 3.5 times the mass of the pre-modified polyamide solution, filter and dry at 55°C for 12 hours to obtain a modified polyamide; (4) Multi-walled carbon nanotubes and 68wt% concentrated nitric acid were mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and then washed with pure water for 7 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride were mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran for 5 times, and dried at 55°C for 12h to obtain pretreated multi-walled carbon nanotubes; pretreated multi-walled carbon nanotubes, tea polyphenols, ethyl acetate, and pyridine were mixed in a mass ratio of 1:4:50:0.1 The mixture was homogenized, reacted at 70°C for 8h, centrifuged at 9500r / min after the reaction, the precipitate was removed, washed with pure water for 3 times, and dried at 55°C for 12h to obtain pre-modified multi-walled carbon nanotubes; the pre-modified multi-walled carbon nanotubes, 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol, acetic acid ethanol solution, and formaldehyde aqueous solution were mixed in a mass ratio of 1:5.5:3.5, reacted at 80°C for 3.5h, filtered, washed with pure water for 3 times, and dried at 55°C for 12h to obtain modified multi-walled carbon nanotubes; (5) Modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent were weighed in a mass ratio of 100:4:0.8, and the modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent were dried at 105°C for 24 hours, and then melt-spun on a high-speed spinning machine. The melt-spinning process parameters were as follows: spinning temperature of 270°C, winding speed of 4500 m / min, and draft ratio of 1.25 to obtain antistatic fibers, which were then woven into antistatic fabrics. Example 3
[0021] A method for preparing an antistatic fabric, comprising the following steps: (1) Weigh polyamide and 2-chloro-6-vinylpyridine in a mass ratio of 1:2.5, mix polyamide and n-propanol in a mass ratio of 1:20 to obtain a polyamide solution, mix 2-chloro-6-vinylpyridine, benzoyl peroxide and n-propanol in a mass ratio of 1:0.03:30 to obtain a vinyl solution, add the vinyl solution dropwise to the polyamide solution at 85°C at a dropping speed of 1 mL / min, stir for 2 h after the addition is completed, add acetone 150 times the mass of the polyamide, filter and dry at 50°C for 12 h to obtain a pyridine-based polyamide; (2) Pyridine polyamide, 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, bis(triphenylphosphine)palladium dichloride, sodium carbonate, tetrahydrofuran and pure water were mixed in a mass ratio of 1:3.0:3.3:5.5:40:10, heated to 90°C for 10 hours under nitrogen protection, and after the reaction, extracted with ethyl acetate, dried over anhydrous sodium sulfate, and evaporated under reduced pressure to obtain methoxy polyamide; methoxy polyamide and dichloromethane were mixed in a mass ratio of 1:2 0 to obtain a methoxy polyamide solution, boron tribromide and dichloromethane are mixed at a mass ratio of 1:20 to obtain a boron tribromide solution, the boron tribromide solution is added dropwise to the methoxy polyamide solution at -52°C under nitrogen protection, and stirring is started at a dropping speed of 0.5 mL / min and a stirring speed of 150 r / min, 10 wt% dilute sulfuric acid (3 times the mass of boron tribromide) is added and stirred for 3 min, filtered and vacuum dried for 12 h to obtain a pre-modified polyamide; (3) Weigh pre-modified polyamide and 2-(diphenylphosphine)benzaldehyde in a mass ratio of 1:3.5, mix pre-modified polyamide, potassium carbonate and N,N-dimethylformamide in a mass ratio of 1:3.5:20, heat to 90°C and stir for 3 hours to obtain a pre-modified polyamide solution, mix 2-(diphenylphosphine)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain a 2-(diphenylphosphine)benzaldehyde solution, add the 2-(diphenylphosphine)benzaldehyde solution dropwise to the pre-modified polyamide solution at a dropping rate of 1 mL / min, continue to react at 90°C for 3 hours after the addition is completed, cool to room temperature, add pure water 12 times the mass of the pre-modified polyamide, cool to 0°C and let stand for 2 hours, add acetone 4 times the mass of the pre-modified polyamide solution, filter and dry at 50°C for 12 hours to obtain a modified polyamide; (4) Multi-walled carbon nanotubes and 68wt% concentrated nitric acid were mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and then washed with pure water for 7 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride were mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran for 5 times, and dried at 50°C for 12h to obtain pretreated multi-walled carbon nanotubes; pretreated multi-walled carbon nanotubes, tea polyphenols, ethyl acetate, and pyridine were mixed in a mass ratio of 1:4:50:0 .1, and react at 70°C for 8h. After the reaction, centrifuge at 9500r / min, remove the precipitate, wash it with pure water for 3 times, and dry it at 50°C for 12h to obtain pre-modified multi-walled carbon nanotubes; pre-modified multi-walled carbon nanotubes, 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol, acetic acid ethanol solution, and formaldehyde aqueous solution are mixed in a mass ratio of 1:6:4, react at 80°C for 3h, filter, wash it with pure water for 3 times, and dry it at 50°C for 12h to obtain modified multi-walled carbon nanotubes; (5) Modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent were weighed in a mass ratio of 100:5:0.9, and the modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent were dried at 105°C for 24 hours, and then melt-spun on a high-speed spinning machine. The melt-spinning process parameters were as follows: spinning temperature of 260°C, winding speed of 4500 m / min, and draft ratio of 1.25 to obtain antistatic fibers, and the antistatic fibers were woven into antistatic fabrics.
[0022] Comparative Example 1: The preparation method of the antistatic fabric of Comparative Example 1 is different from that of Example 2 in that step (3) is not included, and step (2) is modified as follows: pyridine polyamide, 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, bis(triphenylphosphine)palladium dichloride, sodium carbonate, tetrahydrofuran, and pure water are mixed in a mass ratio of 1:2.7:3.0:5.2:35:9, and the mixture is heated to 90° C. under nitrogen protection for 11 hours. After the reaction is completed, the mixture is extracted with ethyl acetate, dried over anhydrous sodium sulfate, and evaporated under reduced pressure to obtain methoxy polyamide. ; Mix methoxy polyamide and dichloromethane in a mass ratio of 1:20 to obtain a methoxy polyamide solution, mix boron tribromide and dichloromethane in a mass ratio of 1:20 to obtain a boron tribromide solution, under nitrogen protection, at -52°C, add the boron tribromide solution dropwise to the methoxy polyamide solution and start stirring, the dropping speed is 0.5 mL / min, the stirring speed is 150 r / min, 10 wt% dilute sulfuric acid (3 times the mass of boron tribromide) is added and stirred for 3 min, filtered and vacuum dried for 12 h to obtain modified polyamide.
[0023] Comparative Example 2: The difference between the preparation method of the antistatic fabric of Comparative Example 2 and Example 2 is that step (2) is modified to mix pyridine polyamide, 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, bis(triphenylphosphine)palladium dichloride, sodium carbonate, tetrahydrofuran, and pure water in a mass ratio of 1:2.7:3.0:5.2:35:9, and under nitrogen protection, the temperature is raised to 90° C. for reaction for 11 hours. After the reaction is completed, ethyl acetate is used for extraction, and the mixture is dried over anhydrous sodium sulfate, and vacuum rotary evaporation is performed to obtain the pre-modified polyamide.
[0024] Comparative Example 3: The difference between the preparation method of the antistatic fabric of Comparative Example 3 and Example 2 is that step (4) is modified as follows: multi-walled carbon nanotubes and 68wt% concentrated nitric acid are mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and then washed with pure water 7 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride are mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran 5 times, and dried at 55°C for 12h to obtain pretreated multi-walled carbon nanotubes; pretreated multi-walled carbon nanotubes, tea polyphenols, ethyl acetate, and pyridine are mixed in a mass ratio of 1:4:50:0.1, reacted at 70°C for 8h, and after the reaction, centrifuged at 9500r / min, the lower precipitate is removed, washed with pure water 3 times, and dried at 55°C for 12h to obtain modified multi-walled carbon nanotubes.
[0025] Comparative Example 4: The preparation method of the antistatic fabric of Comparative Example 3 differs from that of Example 2 in that step (4) is not included, and step (5) is modified as follows: modified polyamide and inorganic silver ion antibacterial agent are weighed in a mass ratio of 100:0.8, the modified polyamide and inorganic silver ion antibacterial agent are dried at 105° C. for 24 h, and then melt-spinned on a high-speed spinning machine. The melt-spinning process parameters are as follows: spinning temperature of 270° C., winding speed of 4500 m / min, and draft ratio of 1.25 to obtain antistatic fibers, and the antistatic fibers are woven to obtain antistatic fabrics.
[0026] Test Example 1: Flame retardant performance test: Test method: The antistatic fabrics prepared in all comparative examples and embodiments were tested for limiting oxygen index using an intelligent oxygen index tester according to GB / T 5454-1997 "Textile Combustion Performance Test Oxygen Index Method", and the results are shown in Table 1.
[0027] Table 1
[0028] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the antistatic fabric prepared by the present invention has good flame retardant properties.
[0029] By comparing the limiting oxygen index of Examples 1 to 3, which is greater than the limiting oxygen index of Comparative Example 1, it is explained that the polyamide is grafted with 2-chloro-6-vinylpyridine under the action of an initiator, and then reacts with 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, and then reacts with 2-diphenylphosphobenzaldehyde through the reaction of aldehyde group and amino group to form a nitrogen-phosphorus ligand containing a Schiff base, and the introduction of phosphorus element can give the fabric flame retardant properties.
[0030] Test Example 2: Conductivity test: Test method: According to GB / T 12703, the antistatic fabric placed on the rotating metal platform is discharged for 30 seconds using a 10KV high voltage. When the static voltage is stable, the time and half-life when the induced voltage decays to half are detected. The antistatic effects of the embodiments and comparative examples are evaluated based on the half-life. The results are shown in Table 2.
[0031] Table 2
[0032] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the antistatic fabric prepared by the present invention has good electrical conductivity.
[0033] By comparison, the half-lives of Examples 1 to 3 are shorter than the half-life of Comparative Example 4, indicating that the multi-walled carbon nanotubes first treated with nitric acid and then treated with thionyl chloride are grafted with tea polyphenols, and the σ bonds between the carbon atoms of the multi-walled carbon nanotubes are formed by covalent bonds between carbon atoms, which can provide a certain electronic conductivity, while the π bonds are formed by coplanarly arranged p orbitals, which have a high degree of electron sharing and can form a π electron cloud region, further enhancing the conductive properties of the multi-walled carbon nanotubes, thereby giving the fabric conductive properties.
[0034] Test Example 3: Mechanical properties test: Test method: The breaking strength of the antistatic fibers prepared in the examples and comparative examples was tested using a YG061F electronic single yarn strength tester according to standard GB / T 14344-2008, wherein the clamping length and the stretching rate were 500 mm and 500 mm / min, respectively, and the pre-tension was 10 cN. The results are shown in Table 3.
[0035] UV resistance test: Test method: All antistatic fibers prepared in the examples and comparative examples were laid flat on a sample rack, and the sample rack was placed in a UV light box parallel to the UV lamp tube, with a radiation intensity of 1100 W / m 2 The temperature in the box was 60°C, the humidity was 60%, the fiber was 10 cm away from the lamp, and the irradiation time was 60 hours. After the irradiation, the breaking strength was tested according to the breaking strength test method of the mechanical properties test and the breaking strength retention rate was calculated. The results are shown in Table 3.
[0036] Test of thermal oxidation aging resistance: Test method: The antistatic fibers prepared in all embodiments and comparative examples were laid flat on a sample rack and then placed in an aging box at an aging temperature of 50°C, a relative humidity of 55%, an ozone concentration of 450 pphm, and an aging time of 360 hours. After aging, the breaking strength was tested according to the breaking strength test method of the mechanical property test and the breaking strength retention rate was calculated. The results are shown in Table 3.
[0037] Table 3
[0038] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the antistatic fabric prepared by the present invention has good mechanical properties, UV resistance and thermal oxidation aging resistance.
[0039] By comparison, the breaking strength of Examples 1 to 3 is greater than that of Comparative Examples 1, 3, and 4, indicating that finally, the modified polyamide, the modified multi-walled carbon nanotubes, and the antibacterial agent are melt-spun to obtain antistatic fibers, and the antistatic fibers are woven to obtain antistatic fabrics. The modified polyamide and the modified multi-walled carbon nanotubes both contain ligands that can complex with metal ions. During the melt spinning process, the antibacterial agent provides silver ions to form a cross-linked network between the modified polyamide and the modified multi-walled carbon nanotubes, thereby enhancing the mechanical properties of the fabric.
[0040] The breaking strength retention rate after ultraviolet irradiation of Examples 1 to 3 is greater than the breaking strength retention rate after ultraviolet irradiation of Comparative Example 2, indicating that the polyamide is grafted with 2-chloro-6-vinylpyridine under the action of an initiator, and then reacts with 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester replaces the chlorine on 2-chloro-6-vinylpyridine to graft 2-amino-4-methoxypyrimidine to the ortho position of the N element on pyridine, and the methoxy group is removed by boron tribromide to form a hydroxyl group, and the hydroxyl group on the pyrimidine and the nitrogen on the pyridine form an intramolecular chelate ring, which can convert light energy into heat energy when subjected to ultraviolet irradiation, thereby giving the fabric anti-ultraviolet performance.
[0041] The breaking strength retention rates after thermal oxidative aging of Examples 1 to 3 are greater than those of Comparative Examples 3 and 4, indicating that the surface of the multi-walled carbon nanotubes treated with nitric acid is carboxylated, and then treated with thionyl chloride so that the surface of the multi-walled carbon nanotubes contains acyl chloride groups, and the acyl chloride groups react with the phenolic hydroxyl groups on the tea polyphenols, thereby grafting tea polyphenols on the surface of the multi-walled carbon nanotubes. Tea polyphenols, as a natural polyphenol substance, have good antioxidant properties and can impart good antioxidant properties to the fabric. Tea polyphenols react with 4-[2,2':6',2''-terpyridine]-4'-yl-thiophenol under the action of formaldehyde, replacing the hydrogen atoms at the C6 and C8 positions of the tea polyphenol A ring. The steric hindrance provided by 4-[2,2':6',2''-terpyridine]-4'-yl-thiophenol allows the ortho-hydroxyl groups to capture free radicals and then shield the formed free radicals, preventing them from initiating a new oxidation cycle again, thereby further improving the antioxidant properties of the fabric.
[0042] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An antistatic fabric, characterized in that: The antistatic fabric is obtained by melt spinning modified polyamide, modified multi-walled carbon nanotubes and inorganic silver ion antibacterial agent; The modified polyamide is obtained by grafting 2-chloro-6-vinylpyridine onto polyamide, reacting with 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, removing the methoxy group by boron tribromide, and reacting with 2-diphenylphosphobenzaldehyde; The modified multi-walled carbon nanotubes are obtained by grafting tea polyphenols onto multi-walled carbon nanotubes treated with nitric acid and then thionyl chloride, and then reacting with 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol.
2. A method for preparing an antistatic fabric, characterized in that: The method comprises the following preparation steps: (1) Weigh polyamide and 2-chloro-6-vinylpyridine in a mass ratio of 1:(2.0-2.5), mix polyamide and n-propanol in a mass ratio of 1:20 to obtain a polyamide solution, mix 2-chloro-6-vinylpyridine, benzoyl peroxide and n-propanol in a mass ratio of 1:(0.02-0.03):(20-30) to obtain a vinyl solution, add the vinyl solution dropwise to the polyamide solution at 85-95°C at a dropping speed of 1 mL / min, stir for 2-2.5 h after the addition is completed, add acetone in an amount of 120-150 times the mass of the polyamide, filter and dry at 50-60°C for 12 h to obtain a pyridine-based polyamide; (2) Pyridine polyamide, 2-amino-4-methoxypyrimidine-5-boric acid pinacol ester, bis(triphenylphosphine)palladium dichloride, sodium carbonate, tetrahydrofuran and pure water were mixed in a mass ratio of 1:(2.5-3.0):(2.7-3.3):(5-5.5):(30- 40): (8-10) mixing, under nitrogen protection, heating to 90 ° C for 10-12h, after the reaction, extracting with ethyl acetate, drying with anhydrous sodium sulfate, and vacuum rotary evaporation to obtain methoxy polyamide; methoxy polyamide and dichloromethane are mixed at a mass ratio of 1:20 to obtain a methoxy polyamide solution, and boron tribromide and dichloromethane are mixed at a mass ratio of 1:20 to obtain a boron tribromide solution, under nitrogen protection, at -52 ° C, the boron tribromide solution is added dropwise to the methoxy polyamide solution and stirring is started, the dropping speed is 0.5 mL / min, the stirring speed is 150 r / min, 10wt% dilute sulfuric acid with a mass of 3 times that of boron tribromide is added and stirred for 3 min, filtered and vacuum dried for 12 h to obtain a pre-modified polyamide; (3) Weigh pre-modified polyamide and 2-(diphenylphosphino)benzaldehyde in a mass ratio of 1:(3-3.5), mix pre-modified polyamide, potassium carbonate, and N,N-dimethylformamide in a mass ratio of 1:(3-3.5):20, heat to 90-100°C and stir for 3-4h to obtain a pre-modified polyamide solution, mix 2-(diphenylphosphino)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain 2-(diphenylphosphino)benzaldehyde. aldehyde solution, adding 2-(diphenylphosphine)benzaldehyde solution to the pre-modified polyamide solution at a dropping speed of 1 mL / min, continuing to react at 90-100°C for 3-4 hours after the dropping is completed, cooling to room temperature, adding pure water 10-12 times the mass of the pre-modified polyamide, cooling to 0°C and standing for 2-3 hours, adding acetone 3-4 times the mass of the pre-modified polyamide solution, filtering and drying at 50-60°C for 12 hours to obtain modified polyamide; (4) Pre-modified multi-walled carbon nanotubes, 4-[2,2':6',2''-terpyridine]-4'-yl-benzenethiol, acetic acid ethanol solution, and formaldehyde aqueous solution were mixed in a mass ratio of 1:(5-6):(3-4), reacted at 80°C for 3-4 hours, filtered, washed with pure water for 3-4 times, and dried at 50-60°C for 12 hours to obtain modified multi-walled carbon nanotubes; (5) Weighing modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent in a mass ratio of 100:(3-5):(0.7-0.9), drying the modified polyamide, modified multi-walled carbon nanotubes, and inorganic silver ion antibacterial agent at 105°C for 24 hours, and then melt-spinning them on a high-speed spinning machine to obtain antistatic fibers, and weaving the antistatic fibers to obtain antistatic fabrics.
3. The method for preparing an antistatic fabric according to claim 2, characterized in that: The polyamide model in step (1) is PA6.
4. The method for preparing an antistatic fabric according to claim 2, characterized in that: The preparation method of the pre-modified multi-walled carbon nanotubes in step (4) is as follows: pre-treated multi-walled carbon nanotubes, tea polyphenols, ethyl acetate and pyridine are mixed in a mass ratio of 1:4:50:0.1, reacted at 70°C for 8 hours, and after the reaction, centrifuged at 9500r / min, removed the precipitate, washed with pure water for 3-4 times, and dried at 50-60°C for 12 hours to obtain pre-modified multi-walled carbon nanotubes.
5. The method for preparing an antistatic fabric according to claim 2, characterized in that: The melt spinning process parameters of step (5) are as follows: a spinning temperature of 260-280° C., a winding speed of 4500 m / min, and a draft ratio of 1.25; and the inorganic silver ion antibacterial agent model is DAW502.
6. The method for preparing an antistatic fabric according to claim 4, characterized in that: The preparation method of the pretreated multi-walled carbon nanotubes is as follows: multi-walled carbon nanotubes and 68wt% concentrated nitric acid are mixed at a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and then washed with pure water for 7-8 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride are mixed at a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran for 5-6 times, and dried at 50-60°C for 12h to obtain pretreated multi-walled carbon nanotubes.
7. The method for preparing an antistatic fabric according to claim 6, characterized in that: The multi-walled carbon nanotube model is L-MWNT-1020.
Citation Information
Cited By
Antistatic modified polyamide fiber and preparation method thereof
CN120174504A